CORRELATIONS BETWEEN TRAP 5 BIOMARKER LEVELS AND THE EXISTENCE OF PERIAPICAL LESIONS IN THE ENT CANCER PATIENT - Cristina Antohi; Anca Melian; Yllka Decolli; Cristina Gena Dascalu; Roxana Mihaela Popescu; Bogdan Ionut Dobrovat; Gianina Bandol; Dragos Iancu; Greta Alexe; Gianina Dodi; Danisia Haba (Romanian Society of Oral Rehabilitation, 2022)
Objectives: The aim of this study was to was to count the number of endo-periodontal lesions in ENT cancer patients, as all patients included in the study will benefit from radio and chemotherapy. Materials and methods: our study included 33 cancer patients with ENT and 30 healthy persons. Both the cancer patient group and the control group were examined by two radiologists, an endodontist and an ENT doctor. We took blood samples to correlate the presence, the size of the periapical lesions by using OPT and CBCT with the bone resorbtion biomarker TRAP- 5. Results: Evaluating the OPT, the depth of the periapical lesions found in the control group varies between 0 and 5.00 mm, with an average of 0.700 ± 1.3859; in the ENT cancer group the size of the periapical lesions also varies between 0 and 6.00 mm, but with an average of 1,664 ± 2,1383, obviously and statistically significantly higher than in the control group. The evaluation of CBCT 3D shows in the control group the maximum size found for periapical lesions is 7.60 mm, with an average of 1.1867 ± 2.20043, and in the ENT cancer group the maximum size for periapical lesions found is 10.81 mm, with an average almost three times higher than in the control group, 3.1658 ± 3.54104. The mean value for TRAP 5B in cancer patients is 0.3539 ± 0.0195, significantly higher than the mean observed in the control group of 0.3034 ± 0.0144. Discussions: There are statistically significant differences between the control group and the group of cancer patients in terms of the size of the observed periapical lesions, assessed by both OPT investigation and CBCT 3D. The evaluation of CBCT 3D highlights the same phenomenon, but the magnitude of the periapical lesions found is higher, both in the control group and in the ENT cancer group. Regarding the comparative evaluations of the results obtained by the ELISA kit, TRAP 5B, in healthy patients compared to those with cancer, there are statistically significant differences. Conclusions: By using CBCT, several periapical lesions were found in the same patients and significant differences were observed in their size. We can say that there is a correlation between the presence of periapical lesions and the values ​​of the biomarker TRAP 5B.